Filiviruses of southeast Asia, China and Europe (review) - A. M. Porshakov; Yu. V. Kononova; T. M. Luong (Журнал инфектологии, 2019)
Filoviruses are known as causative agents of severe haemorrhagic fevers with a high mortality rate in humans. Zaire ebolavirus and Marburgvirus, the most known of them, are associated with the occurrence of sporadic cases and outbreaks of hemorrhagic fevers in some parts of Africa. Isolation of Reston ebolavirus in 1989 in the United States from samples of dead cynomolgus monkeys imported from the Philippines was the first evidence on the existence of filoviruses outside the Africa. Due to the development of new diagnostic methods, Reston ebolavirus or its markers (RNA, antibodies) were found in different animals in the Philippines, China and some other countries of Southeast Asia. These events significantly changed the concept of the geography of filoviruses at present time. Novel filoviruses have been identified in bats in China using of molecular genetic methods. Detection of filovirus RNA (the Lloviu virus) in samples from dead common bent-winged bats in Spain (2002) and in Hungary (2016) indicates the possibility of circulation of filoviruses with unknown pathogenicity potential for humans and animals among bats of temperate latitudes. This review summarizes data on findings of filovirus markers in animals in Southeast Asia, China and Europe.